Enzalutamide and abiraterone in the treatment of patients with metastatic castration-resistant prostate cancer treated previously with chemotherapy - Al-Samsam, S; Bartoš, J; Šámal, V; Dvořák, J; Kolářová, H; Richter, I (Klinicka onkologie, 2023)
BACKGROUND: The evaluation of treatment outcomes and toxicity in patients with metastatic castration-resistant prostate cancer (mCRPC) treated by enzalutamide or abiraterone after previous docetaxel. PATIENTS AND METHODS: We analyzed 66 patients with mCRPC treated by enzalutamide (55 patients) or abiraterone (11 patients) after previous therapy with docetaxel. The median follow-up was 31.2 months. Enzalutamide and abiraterone were administered in daily doses of 160 mg and 1,000 mg per day, respectively. The progression free survival (PFS) and overall survival (OS) were estimated by Kaplan-Meier analysis. The prognostic influence of the factors on OS was evaluated by regression analysis. RESULTS: The progression was observed in 55 (83%) patients, and mPFS was 12.1 (95% CI 7.7-16.4) months. In total, 43 patients died, and he median OS was 21.9 (95% CI 12.2-31.7) months. In the regression analysis, we observed statistical favorable influence of the following factors on OS: PSA decrease ≥ 50%, in patients with early decrease of prostatic specific antigen (PSA) ≥ 50% in 3 months after initiation of enzalutamide or abiraterone treatment, in patients with visceral metastatic sites, in patients treated with only one regimen of previous chemotherapy and in those without anemia. We observed the toxicity grades 3-4 in 45.5% and 36.3% patients treated with enzalutamide and abiraterone, respectively. CONCLUSION: Our analysis demonstrated efficacy and good tolerance in patients with mCRPC treated with enzalutamide and abiraterone after previous docetaxel therapy.
Keywords: Prostatic Neoplasms, Castration-Resistant; Humans; Chemotherapy; targeted therapy; androgen receptor; Prostate-Specific Antigen; lidé; metastases; enzalutamide; nádory prostaty rezistentní na kastraci; docetaxel; Docetaxel; Male; prostatický specifický antigen; castration-resistant prostate cancer; mužské pohlaví; chemotherapy; abiraterone; neoplasm metastasis